P032 MiR-511 deficiency aggravates T cell transfer colitis in mice. (27th May 2021) - Rahman, S; Elfiky, A; van Hamersveld, P H P; Verseijden, C; Welting, O; Meijer, S L; Hakvoort, T B M; de Jonge, W J; Heinsbroek, S E M
Abstract: Background: MiR-511 is embedded in intron region 5 of the CD206/MRC1 gene, expressed by macrophage and dendritic cell populations. In this study, we aimed to investigate the effect of MiR-511 deficiency on intestinal inflammation in a murine T cell transfer colitis model. Methods: A double MiR-511- and Rag-1 (knockout) KO mouse was generated and a T cell transfer colitis was induced by intraperitoneal injection of naïve T cells from donor WT mice. Since these mice lack mature T and B cells, first signs of inflammation appeared at week 3 after T cell injection. An endoscopy score was obtained to determine inflammation at week 3 and 5, respectively. The experiment was terminated at week 5 and severity of inflammation was assessed on the basis of weight loss, colon weight/length ratio, histology score, spleen weight and disease activity index. In addition, flow cytometry was performed for analysing immune cell populations (monocyte, macrophages, dendritic cells, neutrophils) in the colons of both control and colitis groups and T cells in the spleens of colitis group, respectively. Results: Following the induction of T cell transfer colitis, colon weight/length ratio, spleen weight and endoscopic score were significantly increased in the double KO mice compared to Rag-1 KO control mice. A higher histology score and disease activity index in the double KO with no change in weight loss compared to Rag-1 KO control mice was observed. A significant increase in monocyte population in the colons of double KO was seen and increased numbers of monocytes was also observed in the double KO control group with no inflammation. Also, a higher influx of T cells in the double KO mice with a significant increase in Foxp3 and IL4 population was observed in the group with colitis. Conclusion: MiR-511 deficiency aggravates intestinal inflammation compared to Rag-1 KO control mice. Also, a higher presence of monocyte as well as T cell populations were observed in these mice. Together these data show that MiR-511 is involved in the regulation of intestinal health. Future research will focus on underlying mechanisms.